Strategi Komunikasi Pemasaran Pit-Stop Kopi KIG Gresik dalam Mempertahankan Loyalitas Pelanggan - Rama Purba Dewa; Didik Tranggono (Jurnal Nomosleca, 2022)
Pit-Stop  Kopi  KIG  is  one  of  the  cafes  with  the nuances  of  a  warung  in  Gresik  Industrial  City  which  was established in2019. This consumer cafe continues to increase every  year. With  various  marketing  communication  strategies used. This    study aims to determine the marketing communication strategy of Pit-Stop Kopi (KIG) Gresik in maintaining  customer loyalty. This study uses a descriptive approach by collecting  factual  data  based  on  the  results  of observations, study documentation, interviews with area supervisors, and the creative director of Pit-Stop KIG accompanied by five loyal customers, five new customers and one  expert informant  to  complete  the  research data. The selected subjects used in-depth interview techniques. The results showed that Pit-Stop Kopi did a marketing communication strategy to maintain customer  loyalty. The marketing communication strategy taken is advertising, promotion,  service,  product,  place,  physical evidence and process. This KIG Pit-stop also determines the communication channel for ordering by using interpersonal, impersonal channels, and determines the consumer aspect.Keywords: Strategy, Marketing Communication, Consumer Loyalty, Coffee Shop